Bioműanyag lebomlási idejének vizsgálata a Balatonban és partvonalán - Luketics, Nóra; Anda, Angéla; Simon, Brigitta (GEORGIKON FOR AGRICULTURE, 2020)
Nowadays the amount of plastics has been increased world-wide so much that many of us do not recognise its un-naturality. The significant part of the plastics gets back to the environment after using, where it can take up to several hundred years to decompose. In our study, we have been monitored the decomposition rates of bioplastic bags, with a leaf litter bag method in the Keszthely-Bay (Lake Balaton). The study took place between 29.03.2018 and 25.02.2019, both in water and dry land. Our results show, that the bioplastics were in the „slow” decomposition category. We found that samples in the aquatic environment degrade more quickly than on the dry land, still their halving-time is several years.
Keywords: plastic; decomposition; Lake Balaton